Postpartum Depression; A Survey of Mothers Attending Paediatric Outpatient Department in A Tertiary Care Centre: Life Sciences-Paediatrics - Saraga, Karra; Charan, Melachuru Sai Padma; Ramchandran , S; Sujatha, Balamma (International Journal of Life Science and Pharma Research, 2023)
Postpartum maternal depression (PPD) prevalence is around 15-20% in low- and middle-income group countries, and it harms the mother and child unit The aim of the study was to find the prevalence of Postpartum maternal depression in mothers attending Paediatric Out Patient Department OPD and to find if there is any correlation with Socio-Economic-Status SES, maternal health condition, pregnancy or obstetric complication, gender of the child, etc. with postpartum depression. A total of 200 mothers attending the pediatric OPD of a tertiary care hospital in a sub-urban area of South India were enrolled. They were interviewed with a semi-structured questionnaire. Details regarding demographic details, education level, employment, marital status, type of family, availability of help to look after the child and to do household chores, substance use in the family members, mental and physical abuse experienced by the mother, if any. Details of psychiatric illness in the family or history of previous postpartum depression were also collected. Screening for postpartum depression was done using Edinburgh postnatal depression scale. The prevalence of PPD was 9%, and interference with child rearing and perception of difficulty in daily activities were significantly associated with PPD. PPD is an underdiagnosed condition. Mothers can be easily screened for pediatric OPD, and treatment can be offered, leading to healthy mothers and children.